Personality and the dynamism of expression of emotions in marriage - Anna, Linek (Studia Psychologica: Theoria et praxis, 2004)
An attempt at finding relationships between personality and the dynamism of expression of emotions in marriage is the main subject of this article. The issue of emotions has been situated in the centre of research for last few years. Emotions are extremely important factor for all interpersonal relationships, especially for marriage. The dynamism of expression of emotions is defined by the author of this article as a process that means frequency of expressing of positive and negative emotions to spouse and by spouse. The author’s own questionnaire to measure this frequency (Expressing of Emotions in Marriage Scale) was used in this research. Personality is analysed on the basis of the one of the most popular contemporary conception by Costa and McCrae, which treats personality in terms of features. Their model includes five main factors: neuroticism, extraversion, openness to experience, agreeableness and conscientiousness. These features are part of Costa and McCrae Personality Inventory (NEO-FFI) that was used in the research. The reviews of research on this subject and results with analysis of author’s own research are presented in the article.